Accelerating advancing layer viscous mesh generation for 3D complex configurations. (July 2019) - Wang, Zhi; Quintanal, Jaime; Corral, Roque
Abstract: This paper describes the implementation of an efficient and robust advancing layer viscous mesh generation method for complex 3D configurations. The method employs a pre-processing algorithm to identify cells that can be generated without further checking, whereas the rest of the cells are checked by a standard layer-by-layer procedure. This method significantly reduces the number of proximity/intersection checking operations, substantially decreasing the mesh generation wall-clock time while maintaining the same robustness and quality of the baseline method. The practicability of the algorithm is demonstrated using examples of industrial complexity. Mesh generation time is reduced typically by a factor which oscillates between four and ten, with respect to the conventional advancing layer method. This factor grows with the number of layers and depends on the complexity and topology of the domain. This approach has proved to be useful for large size 3D complex configurations where mesh generation time and interactivity are crucial. Highlights: Novel approach to generate hybrid grids for aerodynamic is proposed. 4 and 10 times faster than the standard Advancing-Layer methods. Computational cost saving based on a reduction of the checking operations. Robustness and mesh quality obtained similar to Advancing-Layer methods. Approach useful for large size 3D complex configurations.